HUBUNGAN ANTARA SOSIAL BUDAYA DENGAN PEMBERIAN ASI EKSLUSIF DI PUSKESMAS MANGKUPALAS SAMARINDA - Johan, Herni; Sorta Llyod, Stephanie (Jurnal Kebidanan Mutiara Mahakam, 2016)
DHS data on breastfeeding in 2016 showed that 32% of infants under 6 months exclusively breastfed, while exclusive breastfeeding in East Borneo coverage by 60.06% and in Samarinda by 63%. Mangkupalas health centre attainment of exclusive breastfeeding for 52.5%, still less than the minimum target of 90%. Still a social custom to give additional food to infants before the age of four months. The research was carried out in the working area Mangkupalas health centre Samarinda in order to determine whether there is a relationship between the socio-cultural with breastfeeding infants in the region of Samarinda. The design of this study was an observational analytic supported with quantitative and qualitative data. This study is cross sectional. The population was all mothers who have babies born in January up to April 2016 in the working area Mangkupalas health centre Samarinda, as many as 282 people. Systematic sampling with sampling methods, and Bivariate Data were analyzed statistically using the product moment correlation test, with significance level of p <0.05. The results showed no significant relationship (p <0.05) between the social culture with breastfeeding in the work area Mangkupalas health centre. Based on the results of the study suggested the need for family support both husbands, parents / in-law, shamans and other community so that mothers exclusively breast feed the baby. Health care workers should be able to dig up the existing socio-cultural approach to society through religious leaders, community leaders, traditional birth and other community so as to assist the implementation of exclusive breastfeeding in infants.